2020
DOI: 10.1021/acs.analchem.0c02025
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Imaging Combined with Metabolomics Revealing the Proliferative Effect of Environmental Pollutants on Multicellular Tumor Spheroids

Abstract: Multicellular tumor spheroids (MCTS) have gained increasing attention in cancer research because they may closely mimic some physiological characteristics of solid tumors. MCTS have been considered as a useful three-dimensional cell model for evaluating the effect of exogenous molecules on tumor progression. However, little is known about the metabolic response in MCTS after exposure to exogenous molecules. Herein, we applied metabolomics combined with MALDI-mass spectrometry imaging (MSI) to investigate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI) is an attractive technique used for targeted and untargeted spatial imaging of various biomolecules in tissues. The application spans from medical and biomedical research studies, clinicopathology imaging to drug research and development. , Building on the pioneering studies of Karas et al and Tanaka et al in MALDI MS, this technology has improved markedly from its inception with the introduction of high-mass and high-spatial resolution equipment capable of 1–10 μm resolution. , The upsurge of this label-free technique has been used for both qualitative and quantitative analyses of diverse compounds ranging from small molecule metabolites to peptides and proteins, , as well as drugs , and environmental pollutants in various complex samples. MALDI MSI has become a powerful molecular imaging tool to bridge the gap between the histomorphology and individual molecules in the micro/nanoscale and provides new insights into the tissue-specific metabolism in the occurrence and development of various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI) is an attractive technique used for targeted and untargeted spatial imaging of various biomolecules in tissues. The application spans from medical and biomedical research studies, clinicopathology imaging to drug research and development. , Building on the pioneering studies of Karas et al and Tanaka et al in MALDI MS, this technology has improved markedly from its inception with the introduction of high-mass and high-spatial resolution equipment capable of 1–10 μm resolution. , The upsurge of this label-free technique has been used for both qualitative and quantitative analyses of diverse compounds ranging from small molecule metabolites to peptides and proteins, , as well as drugs , and environmental pollutants in various complex samples. MALDI MSI has become a powerful molecular imaging tool to bridge the gap between the histomorphology and individual molecules in the micro/nanoscale and provides new insights into the tissue-specific metabolism in the occurrence and development of various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Another typical application of MALDI-MSI is the analysis of exogenous components in various tissues. It has been reported that the persistent organic pollutant PFOSs could induce oxidative damage to the kidneys of mice . Herein, the mouse kidney deposited with PFHxS/PFOSs via the dry droplet method was used as a model to assess the sublimator for MALDI-MSI.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, MSI makes it possible to look into diagnosis and prognosis of disease in an innovative way [ 20 , 21 ]. Data generated from MSI could provide information of metabolic response in tumor tissues, thus enabling a deeper exploration of tumor microenvironment [ 22 , 23 ]. In the past few years, researchers have attempted to observe the localization of endogenous metabolites in plant tissues using MSI [ 24 ].…”
Section: Introductionmentioning
confidence: 99%